2022
DOI: 10.3389/fcimb.2022.806077
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequencing and Reverse Transcriptase PCR Reveal That Mobile Phones and Environmental Surfaces Are Reservoirs of Multidrug-Resistant Superbugs and SARS-CoV-2

Abstract: BackgroundMobile phones of healthcare workers (HCWs) can act as fomites in the dissemination of microbes. This study was carried out to investigate microbial contamination of mobile phones of HCWs and environmental samples from the hospital unit using a combination of phenotypic and molecular methods.MethodsThis point prevalence survey was carried out at the Emergency unit of a tertiary care facility. The emergency unit has two zones, a general zone for non-COVID-19 patients and a dedicated COVID-19 zone for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Yet despite such attempts at trying to maintain a sanitised mobile phone, studies have shown that contamination with microbes can occur instantaneously. Recently, our research team highlighted the presence of SARS-CoV-2 on the mobile phone of a HCW although the phone was wiped, within the preceding 24 h with 70% isopropyl [18].…”
Section: Discussionmentioning
confidence: 99%
“…Yet despite such attempts at trying to maintain a sanitised mobile phone, studies have shown that contamination with microbes can occur instantaneously. Recently, our research team highlighted the presence of SARS-CoV-2 on the mobile phone of a HCW although the phone was wiped, within the preceding 24 h with 70% isopropyl [18].…”
Section: Discussionmentioning
confidence: 99%
“…This study was carried out at the Emergency care unit of Rashid Hospital, Dubai, United Arab Emirates, as part a larger study investigating microbial contamination of mobile phones among HCWs. 8 Whilst we had previously published findings on the microbial contamination of mobile phones of 35 HCWs at this facility, 8 the data obtained from HCWs with dual ownership of smart watches and mobile phones was not included in that report as additional sampling was carried out for these individuals. The Ethical approval was obtained from Dubai Scientific Research Ethics Committee, Dubai Health Authority (REF#: DSREC-02/2021_02) and MBRU Institutional Review Board (REF#: MBRU-IRB-2020-040) and consent was obtained from participants as per reported protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The Ethical approval was obtained from Dubai Scientific Research Ethics Committee, Dubai Health Authority (REF#: DSREC-02/2021_02) and MBRU Institutional Review Board (REF#: MBRU-IRB-2020-040) and consent was obtained from participants as per reported protocol. 8 The study was carried out in compliance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…With 134 different antibiotic resistance genes and 419 different virulent factor genes found across all 26 mobile phones, the United Nation sustainable development goal number #3 ‘Good health and well-being’, is in peril. SDG#3 will undoubtfully fail to reach that goal by 2030 because of multiple factors that include: (i) a discovery void era of new antibiotics, (ii) paucity of research for alternative antimicrobial solutions and (iii) ‘third hand’ microbial laden mobile phones with multi drug resistant superbugs 22 . Hundreds of trillions of micro-organisms on the surface of billions of mobile phone fomites cross borders, by means of modern transport, un-noticed as Trojan horses.…”
Section: Author’s Recommendationmentioning
confidence: 99%